Bài 3: Những hằng đẳng thức đáng nhớ

Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Ngọc Thư

a. \(\dfrac{x-1}{x^{2^{ }}-4}=\dfrac{3}{2-x}\)

b. \(\dfrac{1}{x-1}-\dfrac{7}{x-2}=\dfrac{1}{\left(x-1\right)\left(2-x\right)}\)

c. \(\dfrac{2x+3}{2x-3}-\dfrac{3}{4x-6}=\dfrac{2}{5}\)

d. \(\dfrac{x+29}{31}-\dfrac{x+27}{33}=\dfrac{x+17}{43}-\dfrac{x+15}{45}\)

BW_P&A
28 tháng 4 2017 lúc 20:53

a) \(\dfrac{x-1}{x^2-4}=\dfrac{3}{2-x}\)

\(\Leftrightarrow\dfrac{x-1}{\left(x-2\right)\left(x+2\right)}=-\dfrac{3}{\left(x-2\right)\left(x+2\right)}\)

\(ĐKXĐ:\left\{{}\begin{matrix}x\ne2\\x\ne-2\end{matrix}\right.\)

\(\Rightarrow x-1=-3\)

\(\Leftrightarrow x=1-3=-2\)

Vậy: \(x=-2\)

b) \(\dfrac{1}{x-1}-\dfrac{7}{x-2}=\dfrac{1}{\left(x-1\right)\left(2-x\right)}\)

\(\Leftrightarrow\dfrac{1}{x-1}-\left(-\dfrac{7}{2-x}\right)=\dfrac{1}{\left(x-1\right)\left(2-x\right)}\)

\(ĐKXĐ:\left\{{}\begin{matrix}x\ne1\\x\ne2\end{matrix}\right.\)

\(\Leftrightarrow\dfrac{2-x}{\left(x-1\right)\left(2-x\right)}+\dfrac{7\left(x-1\right)}{\left(x-1\right)\left(2-x\right)}=\dfrac{1}{\left(x-1\right)\left(2-x\right)}\)

\(\Rightarrow2-x+7x-7=1\)

\(\Leftrightarrow-x+7x=1-2+7=6\)

\(\Leftrightarrow6x=6\)

\(\Leftrightarrow x=1\)

Vậy: \(x=1\)

c) \(\dfrac{2x+3}{2x-3}-\dfrac{3}{4x-6}=\dfrac{2}{5}\)

\(\Leftrightarrow\dfrac{2x+3}{2x-3}-\dfrac{3}{2\left(2x-3\right)}=\dfrac{2}{5}\)

\(\Leftrightarrow\dfrac{10\left(2x+3\right)}{10\left(2x-3\right)}-\dfrac{3.5}{10\left(2x-3\right)}=\dfrac{4\left(2x-3\right)}{10\left(2x-3\right)}\)

\(ĐKXĐ:x\ne\dfrac{3}{2}\)

\(\Leftrightarrow10\left(2x+3\right)-15=4\left(2x-3\right)\)

\(\Leftrightarrow20x+30-15=8x-12\)

\(\Leftrightarrow20x-8x=15-12-30\)

\(\Leftrightarrow12x=-27\)

\(\Leftrightarrow x=-\dfrac{27}{12}=-\dfrac{9}{4}\)

Vậy: \(x=-\dfrac{9}{4}\)

d) \(\dfrac{x+29}{31}-\dfrac{x+27}{33}=\dfrac{x+17}{43}-\dfrac{x+15}{45}\)

\(\Leftrightarrow\left(\dfrac{x+29}{31}+1\right)-\left(\dfrac{x+27}{33}+1\right)=\left(\dfrac{x+17}{43}+1\right)-\left(\dfrac{x+15}{45}+1\right)\)

\(\Leftrightarrow\dfrac{x+60}{31}-\dfrac{x+60}{33}=\dfrac{x+60}{43}-\dfrac{x+60}{45}\)

\(\Leftrightarrow\dfrac{x+60}{31}-\dfrac{x+60}{33}-\dfrac{x+60}{43}+\dfrac{x+60}{45}\)

\(\Leftrightarrow\left(x+60\right)\left(\dfrac{1}{31}-\dfrac{1}{33}-\dfrac{1}{43}+\dfrac{1}{45}\right)=0\)

\(\Leftrightarrow x+60=0\)\(\left(\dfrac{1}{31}-\dfrac{1}{33}-\dfrac{1}{43}+\dfrac{1}{45}\ne0\right)\)

\(\Leftrightarrow x=-60\)

Vậy: \(x=-60\)

_Good luck to you_